2017
DOI: 10.1088/1361-6641/32/3/035002
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap tuning in GaAs1−xSbxaxial nanowires grown by Ga-assisted molecular beam epitaxy

Abstract: In this work we present a comprehensive study on the effects of Sb incorporation on the composition modulation, structural and optical properties of self-assisted axial GaAs 1−x Sb x nanowires of 2-6 μm in length grown on (111) Si substrate by molecular beam epitaxy. The Sb composition in the GaAs 1−x Sb x axial nanowire (NW) was varied from 2.8-16 at.%, as determined from energy dispersive x-ray spectroscopy. Lower Sb composition leads to thinner nanowires and inhomogeneous Sb composition distribution radiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 42 publications
5
30
1
Order By: Relevance
“…13b in which the relative intensity of the ratio of the LV mode to the normalized TO mode has been plotted as a function of Sb concentration in the NWs. A linear fit resulted in a slope of 2.23, which is comparatively higher than the slope of ~1.2 reported in the literature 20, 22 . The explanation for the observed larger slope in our work is as follows.…”
Section: Resultscontrasting
confidence: 63%
See 2 more Smart Citations
“…13b in which the relative intensity of the ratio of the LV mode to the normalized TO mode has been plotted as a function of Sb concentration in the NWs. A linear fit resulted in a slope of 2.23, which is comparatively higher than the slope of ~1.2 reported in the literature 20, 22 . The explanation for the observed larger slope in our work is as follows.…”
Section: Resultscontrasting
confidence: 63%
“…12b,c) accompanied with a larger FWHM (Fig. 12d) of the spectra for 34 at.% Sb, attesting to the increased incorporation of larger atomic size Sb in the lattice that leads to enhanced disorder-induced strain 22, 33 .
Figure 12XRD spectra of GaAs 1−x Sb x NWs for ( a ) different Sb compositions; ( b ) and ( c ) represent the corresponding GaAsSb (111) and GaAsSb (222) Bragg peaks; ( d ) represent the change in FWHM with Sb at.% variation in the NWs.
…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Sb-induced morphological transformation is not limited to InAsSb NWs and has also been observed in GaAsSb NWs [ 60 , 61 ]. Ren et al [ 46 ] observed that the morphologies of MBE grown GaAsSb NWs are significantly influenced by the Sb flux, whereas, the diameter of the NW increased, the lengths decreased with increasing Sb flux.…”
Section: Surfactant Effect Of Sbmentioning
confidence: 98%
“…A comprehensive study of the effect of Sb incorporation on the composition modulation, structural and optical properties of self-assisted GaAsSb NWs on (111) Si substrate was conducted by Ahmad et al [ 61 ] in 2017 using MBE. The NWs exhibited a pure zinc blende crystal structure, largely free of any planar defects with inverse dependence of NWs density as a function of Sb flux, which was associated with the surfactant effect of Sb and droplet size-dependent Gibbs–Thomson effects [ 62 ].…”
Section: Growth Of Au-free Ternary Iii–as–sb Nanowires Directly Onmentioning
confidence: 99%